Transducer Function In Vending Machine Simulation Design - Tuti Andriani; Pristiwanto (Cattleya Darmaya Fortuna, 2019)
A vending machine is a substitute for a cashier or admin in the form of a machine so that buyers simply enter coins and the machine will issue them according to the request. Moore machine and mealy machines as a process for processing buyer orders which are translated into machine orders. Based on the test results of coins entered 1000 and 500, the drink can be chosen according to the price of the drink.